Perilaku konsumtif ditinjau dari kontrol diri dan celebrity worship penggemar NCT - Amelia Josephin Charistia; Andik Matulessy; Nindia Pratitis (INNER: Journal of Psychological Research, 2022)
The purpose of this study is to determine the correlation between self-control and celebrity worship with the consumptive behavior of NCT fans. This study involved 110 adolescent fans of NCT on Twitter and Instagram users with a population of 150. This study used a quantitative method with the type of correlation. The sampling technique used purposive sampling technique and hypothesis testing using linear regression analysis. Based on the result of data analysis it shows self-control has a significant negative correlation with consumptive behavior with T value -8.232 and significance value 0.000 (p<0.05) meanwhile celebrity worship has a significant positive correlation with consumptive behavior with T value 3.995 and significance value 0.000 (p<0.05). Thus, it can be concluded that the hypothesis in this study is accepted. Keywords: Consumptive Behavior, Self-Control, Celebrity Worship